Avaliação de meios de destinação alternativos para lodo resultante de tratamento de efluentes industriais: estudo de caso em indústria química - Scarin, Priniely Beatriz Reis [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Solid waste represents a worldwide concern when regarding its correct destination and its generation. In the industrial sphere, in addition to demanding greater attention due to the possible hazardousness of these wastes, their correct allocation represents high costs for the responsible companies. As an alternative to soften the problem of solid waste disposal is the application of these in building materials and also in agriculture as fertilizers. Such alternatives are related with the concept of Circular Economy, since the use of these in the civil construction or agriculture sectors would reduce the consumption of raw materials in these sectors. Among the solid industrial wastes with notable research attention is the residual sludge from Wastewater Treatment Plants, where it is often sought to find more sustainable alternatives for their correct disposal. In this sense, the present study had as the main objective to analyze the residual sludge from the Wastewater Treatment Plant of a chemical industry and, using its toxicological classification and the characteristics of the Wastewater Treatment Plant and also the industry, and to propose the best alternatives for the sludge destination. This feasibility study was carried out for the application in ceramic, cement and soil culture materials and used many researches already developed in this area, taking into account the treatment required for the sludge in each of the three methods studied and the results presented after disposal of the waste as well as the quality of the material or fertilizer produced. Finally, the sequence of attractiveness found for the application of the sludge in the studied methods was first the application in ceramic materials, then the application in cultivable soils and finally as cementitious materials, however, a more accurate evaluation on the ...( Complete abstract click electronic access below)

Os resíduos sólidos representam mundialmente uma preocupação no que diz respeito à sua correta destinação e a sua geração. No âmbito industrial, além de demandarem uma atenção maior devido à possível periculosidade desses resíduos, a correta destinação destes representa custos onerosos para as empresas geradoras. Como uma alternativa para amenizar o problema de destinação dos resíduos sólidos encontra-se a aplicação destes em materiais da construção civil e também na agricultura como fertilizantes. Tais alternativas vão de encontro ao conceito de Economia Circular, já que a utilização dessas alternativas nos setores da construção civil ou agricultura reduziria o consumo de matérias primas nesses setores. Entre os resíduos sólidos industriais com notável atenção de pesquisas encontra-se o lodo residual de Estações de Tratamento de Efluentes (ETE), onde frequentemente busca-se encontrar alternativas mais sustentáveis para a correta destinação dos mesmos. Nesse sentido, o presente estudo teve por objetivo analisar o lodo residual da ETE de uma indústria química e, utilizando-se da classificação toxicológica do mesmo e de características da ETE e da indústria geradora, propor as melhores alternativas para a destinação do lodo. Esse estudo de viabilidade foi realizado restringindo-se a aplicações em materiais cerâmicos, cimentícios e em solos cultiváveis. Para tal, utilizou-se como base pesquisas já desenvolvidas nessa área, levando em conta o tratamento necessário para o lodo em cada um dos três métodos estudados e os resultados apresentados após a destinação, tanto no que diz respeito ao tratamento do resíduo como também na qualidade do material ou fertilizante produzido. Por fim, a ordem de atratividade encontrada para aplicação do lodo em questão nos métodos estudados foi ... (Resumo completo, clicar acesso eletrônico abaixo)
Evaluation of alternative means of disposal for sludge resulting from industrial effluent treatment: case study in chemical industry
Keywords: Residuos industriais - Aspectos ambientais; Sustentabilidade; Lodo; Efluente - Qualidade; Factory and trade waste Environmental aspects